Applying project management principles to avoid cost overruns at pt edn - Herbisworo, Rahadian; F.Firman, Aries (The Indonesian Journal of Business Administration, 2019)
Abstract. Today, Infrastructure development in Indonesia is developing. Indonesia is lagging behind in infrastructure, this causes our country to determine high domestic prices because of its complicated and expensive infrastructure. Impressive infrastructure development in the country will improve the economy of the surrounding community. So the community has the opportunity to sell or deliver goods or expand the business at a relatively lower price than before. PT EDN is a contractor company in a toll road infrastructure industry, the scope of work  PT EDN's includes on Cut & Fill and Supply Materials. PT EDN obtained a contract from one of the main contractors as a subcontractor to run the Bogor - Ciawi - Sukabumi Toll Road Project. The methodology of this research was conducted by gathering information about what happened in doing and the results obtained in the BOCIMI project, and this study using a qualitative research method by conducting interviews with stakeholders in the BOCIMI project. While working on the project, many obstacles occur, including planning and making budgets, managing cash flows, and controlling the project. After conducting interviews and data collection, problems arise at PT EDN due to not having an integrated system between one business process and other business processes. Therefore, project management is needed to add value when working on a project, so that operations in the project can works well and can improve the performance of PT EDN. The purpose of this study is to find and identify the cause of cost overruns such as internal and external factors, and to avoid cost overruns in project implementation by applying project management principles. Moreover, the results of the recommendations obtained from this discussion and research for PT EDN are to to applying change management to deal with the change of design by the main contractor, applying risk mitigation, applying project planning management methods and project control management, applying control cost method that can see the cost performance, and develop human resources, with enhanced team collaboration in the project. With these recommendations, it is expected to be a guideline in conducting effective project management with the aim of gaining profit according to the targetKeywords:, Project Management, Project Cost Management, Cost Overruns